The Effect Of Servant Leadership And Distributive Justice On Continuance Commitment - Muhammad Harfiansyah Makarim; Arief Nurrahman (Jurnal Manajemen Kreatif dan Inovasi, 2024)
Commitment becomes a means for organizations to improve organizational performance. Through the support of leaders who use the servant leadership leadership style and the existence of distributive justice in the organization, employee performance will increase. This study aims to analyze: 1) the influence of servant leadership on continuance commitment; 2) the effect of distributive justice on the continuance commitment of Sentana Group employees. This research includes using quantitative research with a cross-sectional approach. The respondents of this study were 58 employees of the Sentana Group. Data on servant leadership, distributive justice, and continuance commitment were obtained using a survey technique using a questionnaire instrument that was validated by experts and reliable based on the results of the trial. The analysis used in this research is descriptive statistical analysis and regression analysis. The results showed that there were: 1) positive and significant influence of servant leadership on continuance commitment; 2) positive and significant influence of distributive justice on continuance commitment. In addition, it is also concluded that servant leadership has a greater influence on continuance commitment than distributive justice.